Study of Gold Mine Tailings Utilization as Fine Aggregate Material for Producing Shotcrete Based on Concept of Green Technology - Lilies Widojoko; Harianto Hardjasaputra; Susilowati SUSILOWATI (Bandar Lampung University (UBL), 2014)
Shotcrete is concrete that is applied by spraying. The use of shotcrete from year-to-year increase. Because sand is a material for the manufacture of shotcrete, the volume of sand will increase as well. Sand excavation on a large scale can lead to disruption of the environment. Reuse of tailings for shotcrete can reduce the volume of sand used. In addition, utilize waste materials will reduce the contamination surrounding environment. This study is a continuation of previous studies, that the use of tailings as conventional concrete manufacture. The results showed that the optimum tailings substitution of 25% both for conventional concrete or shotcrete. Laboratory studies conducted at the Civil Engineering Laboratory of University of Bandar Lampung and PT Semen Baturaja. Research using a shotcrete equipment done in PT Natarang Mining, Way Linggo, Lampung. Type of admixture used is monomer composite material under the trade name Polcon. The compressive strength achieved in the laboratory was 32.7 MPa when not using Polcon as admixture. When using Polcon, the compressive strength reached 33.5 MPa. Crushing compressive strength of shotcrete in the field trial is 20.3 MPa. For studying the micro structure of tailings, cement, mortar with tailings 100%, 50% and without tailings, the Scanning Electron Microscopy micro photo are done.